Particularities of hip arthroplasty and restoration of its function in patients with low bone mass (literature review) - Filipenko, Volodymyr; Bondarenko, Stanislav; Badnaoui, Ahmed; Mezentsev, Volodymyr; Maltseva, Valentyna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. Basing on the analysis of the scientific literature to study the prevalence of osteoporosis and osteopenia among patients with hip osteoarthritis undergoing THA and to establish the influence of osteoporosis/osteopenia on the choice of implants and on the restoration of the joint function after the surgery. Osteoporosis and osteopenia are manifested in 21–32 % patients undergoing hip arthroplasty. Low bone mass may be a cause of intraoperative (periprosthetic hip fractures) and postoperative complications. In patients with low bone mass bone remodeling with an increased resorption and inhibition of bone formation around hip components can lead to increasing of its micro-movements, the formation of fibrous tissues, and diminution of implants survivorship. In patients with normal bone mineral density (BMD) also the loss of bone tissue around the acetabular cup can occur; it can occur up to 20–60 % in the first three years post operation, which can lead to the cup instability. But the dynamics of changes in bone tissue around the acetabular component in patients with osteoporosis/osteopenia is nowadays poorly understood. We suppose that porous acetabular components have advantages in patients with low BMD. Due to the elastic modulus which is closely similar to cancellous bone, as well as the corresponding porosity, which facilitates osteointegration and gives a reliable secondary biological fixation of the acetabulum. Rehabilitation and restoration of kinematic and support function of the hip joint after arthroplasty is an important issue for patients with low BMD. Gait disturbance can persist 12 months after surgery. One of the reasons is the weakness of the muscles of the femur. Rehabilitation after total hip arthroplasty leads to faster recovery, but particularities of rehabilitation in patients with low bone mass are not fully studied.